(untitled) (Sudurpaschim Spectrum, 2026)
This paper examines how digital technologies in Nepal, often embraced as indicators of national development, modernization, digital efficiency, inadvertently reinforce cultural, social, and linguistic hierarchies. By applying Science and Technology Studies (STS) as a critical framework and drawing upon Ruha Benjamin’s concept of the “New Jim Code,” the study explores how the use of digital technologies in Nepal designed in Western contexts marginalize and discriminate communities when applied uncritically in Nepal. Through an interdisciplinary methodology and illustrative case studies, including Nepal’s biometric ID program, skin recognition systems, and language-based digital exclusions, the paper shows how these digital systems disproportionately disadvantage women, rural laborers, and non-dominant language speakers in Nepal. This paper argues that these exclusions are not technical flaws but manifestations of epistemic and cultural disregard. The findings suggest the need for inclusive, decolonial, and locally grounded technological frameworks that prioritize justice over efficiency. Finally, the paper calls for reimagining digital innovation through participatory, context-aware, and equity-centered technological design that not only contributes to the growing discourse on technological inequality in the Global South, but also stresses the need to dovetail digital infrastructures with the lived realities of diverse Nepali communities instead of abandoning technological advancement.